PENERAPAN BAHAN AJAR TRIGONOMETRI DENGAN MODEL MATEMATIKA KNISLEY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIK MAHASISWA - Puji Nurfauziah; Veny Triyana Andika Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The aim of this study is to determine the improvement of students' critical thinking skills in trigonometry courses whose learning uses trigonometric teaching materials with knisley mathematical models compared to those that do not use teaching materials. The method used in this study is quasi-experimental with a sample of fourth semester students. The instrument used in this study is a test of critical thinking skills as much as 5. Based on the results of the data analysis, it can be concluded that the improvement of students' critical thinking skills in learning using trigonometric teaching materials with knisley mathematical models is better than those who do not use teaching materials